2008
DOI: 10.1080/15265160802166017
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethics Education Influence the Moral Action of Practicing Nurses and Social Workers?

Abstract: Ethics education has a significant positive influence on moral confidence, moral action, and use of ethics resources by nurses and social workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
153
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(163 citation statements)
references
References 19 publications
6
153
0
4
Order By: Relevance
“…6, June 2015 Education level of the research sample may have great influences on the overall outcome of these two studies. Education has been widely perceived as one of the most important socio-economic determinants of health and mortality [25]. This is similar to previous study where education level does predict the level of practice and application of the knowledge in daily life [26].…”
supporting
confidence: 87%
“…6, June 2015 Education level of the research sample may have great influences on the overall outcome of these two studies. Education has been widely perceived as one of the most important socio-economic determinants of health and mortality [25]. This is similar to previous study where education level does predict the level of practice and application of the knowledge in daily life [26].…”
supporting
confidence: 87%
“…Although the specific content was not specified, the nurses in the study 32 reported that receiving such training increased their self-confidence in their ethical skills and ability to take moral action. Although controversy exists about the structure and content of ethics education in general, Wocial 33 suggests that it is necessary to move beyond the debate and provide continuing education.…”
Section: Ethical Actionmentioning
confidence: 99%
“…Many nurses receive instruction in ethics as part of their basic educational preparation program. However, the findings of a recent study by Grady et al 32 suggest that continuing education or in-house training is necessary to improve and maintain ethical skills.…”
Section: Ethical Actionmentioning
confidence: 99%
“…A study conducted in the US among nurses and social workers found that participants who had had more ethics education and training felt more confident in their moral judgments and were more likely to use ethics resources, such as ethics consultations, and take moral action (Grady et al 2008). That study only analyzed how nurses and social workers perceived their actions and did not assess real actions or effects on patient outcomes.…”
Section: Healthcare Ethics In Medical Education In Indiamentioning
confidence: 99%